2012
DOI: 10.1021/co200181x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Unique Isoindoline/Tetrahydroisoquinoline-based Tricyclic Sultam Library Utilizing a Heck-aza-Michael Strategy

Abstract: The synthesis of a unique isoindoline- and tetrahydroisoquinoline (THIQ)-containing tricyclic sultam library, utilizing a Heck-aza-Michael (HaM) strategy is reported. Both isoindoline and THIQ rings are installed through a Heck reaction on a vinylsulfonamide, followed by one-pot deprotection and intramolecular aza-Michael reaction. Subsequent cyclization with either paraformaldehyde condensation or 1,1'-carbonyldiimidazole coupling generates a variety of tricyclic sultams. Overall, a 160-member library of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…In Scheme , representative examples of synthetic transformations of vinylsulfonyl derivatives in general, and styrylsulfonyl derivatives in particular, are shown. Isoindole 12 results from the intramolecular conjugate addition of an amine to an α,β‐unsaturated sulfonamide . α,β‐Unsaturated sulfones can be deprotonated selectively at the α position, and then trapped with electrophiles, as shown for the formation of 13 , which results from lithiation of the parent sulfone with MeLi, and alkylation with MeI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Scheme , representative examples of synthetic transformations of vinylsulfonyl derivatives in general, and styrylsulfonyl derivatives in particular, are shown. Isoindole 12 results from the intramolecular conjugate addition of an amine to an α,β‐unsaturated sulfonamide . α,β‐Unsaturated sulfones can be deprotonated selectively at the α position, and then trapped with electrophiles, as shown for the formation of 13 , which results from lithiation of the parent sulfone with MeLi, and alkylation with MeI .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, styrylsulfonyl derivatives can also be accessed through Heck arylation of vinylsulfonyl derivatives. Compared to the plethora of examples of Heck arylations of acrylates, the analogous couplings of vinylsulfones and vinylsulfonic acid derivatives have hardly been explored , . Generally, successful Heck reactions of these substrates require aryl bromides, activating phosphine ligands such as PPh 3 or occasionally P( o ‐tolyl) 3 , reaction temperatures higher than 100 °C, and reaction times of several hours.…”
Section: Introductionmentioning
confidence: 99%
“…8 These efforts include a “click, click, cyclize” strategy in the synthesis of 1,4,5-oxathiazepane 4,4-dioxides utilizing an intramolecular oxa-Michael pathway, 8a,b an automated synthesis of 1,2,5-thiadiazepane 1,1-dioxide via an aza-Michael pathway, 8c a double aza-Michael protocol in the synthesis of 1,2,5-thiadiazepane 1,1-dioxide, 8d.e and a Heck-aza-Michael strategy in the synthesis of isoindoline/tetrahydroisoquinoline-based tricyclic sultams. 8f,g Taken collectively, use of “click” sulfonylation, 9 “click” sulfonamide alkylation and subsequent Michael additions greatly simplify sultam construction. In this context, we herein report a one-pot sulfonylation/intramolecular thia-Michael protocol, which combines the “click” sulfonylation and the cyclization steps in one pot, to readily assemble the titled sultam scaffolds.…”
mentioning
confidence: 99%
“…8 Previous oxa-Michael studies from our laboratories has shown that the use of a tertiary sulfonamide is necessary for the Michael addition to take place. However, when 1 was treated with cysteine ethyl ester ( 2a ) or cysteamine ( 2b ), intramolecular thia-Michael and sulfonylation occur simultaneously, leading to a one-pot synthesis of 1,5,2-dithiazepine 1,1-dioxide scaffolds 3 that bear free sulfonamide N-H groups (Scheme 1).…”
mentioning
confidence: 99%
“…Methods that have been used to prepare these cyclic sulfonamides include the intramolecular Diels–Alder reaction [4], cyclization of aminosulfonyl chlorides [5], cycloadditions [6], radical cyclization [7], transition metal-catalyzed approaches [8], and ring-closing metathesis (RCM) [9]. Moreover, we have developed a variety of methodologies for the generation of five to eight-membered annulated and non-annulated sultams through processes we have termed “Click-Click-Cyclize” [10], “Click-Cyclize” [11], reagent-based DOS [12], “Click, Click, Cy-Click” [13], and Heck, aza-Michael (HaM) strategies [14,15]. …”
Section: Introductionmentioning
confidence: 99%